THE EFFECT OF DIVIDEND POLICY ON STOCK PRICES IN LQ 45 COMPANIES IN INDONESIA - Andini Nurwulandari (SEAN Institute, 2022)
A firm's decision on how it will handle its profits—whether those profits will be paid out to shareholders in the form of dividends or kept in the company so that it can be reinvested—is referred to as its dividend policy. The purpose of this study is to investigate the impact that dividend policies have on the share prices of LQ 45 firms that are listed on the Indonesia Stock Exchange. The data that were used are secondary data that were collected from the financial reports of firms that were listed on the Indonesia Stock Exchange throughout the period of 2017-2021. Multiple linear regression is the type of analysis that is utilized, and the dependent variable that is utilized is stock prices, while the independent variable that is utilized is dividend policy. According to the findings of the research conducted, dividend policies have a constructive and discernible impact on the stock prices of manufacturing companies in Indonesia. In this scenario, corporations that have dividend policies that are more generous tend to have stock prices that are higher.